Prognostic significance of tumor angiogenesis markers in advanced cervical cancer undergoing chemotherapy - Mahendra, I Nyoman Bayu; Winata, I Gde Sastra; Setiawan, William Alexander; Putra, Ida Bagus Agung Widnyana; Darmayasa, Putu Bagus (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Cervical cancer is the second leading cause of cancer-related deaths among women worldwide. Despite advancements in screening programs and vaccination efforts, a significant proportion of patients present with advanced-stage disease, characterized by severe manifestations and a poor prognosis. Clinical evidence highlights substantial variability in the sensitivity of chemotherapy regimens among cervical cancer patients, often resulting in suboptimal therapeutic outcomes and increased risk of complications. This underscores the need for reliable molecular markers to predict prognosis and optimize therapy. Angiogenesis plays a pivotal role in the development and progression of solid tumors, including cervical cancer. Key tumor angiogenesis markers, such as vascular endothelial growth factor (VEGF) and its receptor (VEGFR), are critical in driving tumor progression in advanced cervical cancer. Studies have demonstrated significant correlations between VEGF levels and important prognostic parameters, including tumor size, metastasis, and chemotherapy response. Consequently, tumor angiogenesis markers like VEGF and VEGFR hold potential as valuable predictive tools to guide the management of advanced cervical cancer, particularly in patients undergoing chemotherapy.